The Efficacy of Nebulized Furosemide and Salbutamol Compared with Salbutamol Alone in Reactive Airway Disease: A Double Blind Randomized, Clinical Trial - Kambiz Masoumi; Arash Forouzan; Maryam Haddadzadeh Shoushtari; Samaneh Porozan; Maryam Feli; Mehdi Fallah Bagher Sheidaee; Ali Asgari Darian (Emergency Medicine International)
We undertook this randomized clinical trial to investigate whether adding furosemide to salbutamol could improve the peak expiratory flow rate (PEFR) and clinical signs of reactive airway disease (RAD) patients. Eligible 18- to 55-year-old patients were randomly divided into intervention and control groups. Patients received 5 mg of nebulized salbutamol and 40 mg of nebulized furosemide in the intervention group and 5 mg of nebulized salbutamol alone in the control group. Patients in both groups received 100 mg of methylprednisolone intravenously stat. Severity of the RAD was estimated before and 45 minutes after treatment in both groups. PEFR was estimated before treatment and at 15, 30, and 45 minutes later. Ninety patients were enrolled, 45 in each group. There were no significant differences between two groups regarding gender, mean age, and normalized PEFR. The baseline mean PEFR was not significantly different between groups (P=0.58). A repeated measure analysis of variance revealed that the differences between the two treatments was significant (P=0.0001) and the behavior of two treatments was not similar across the time (P=0.001). Comparison of clinical severity of acute RAD revealed no significant differences between groups at the end of the trial (0.06). This study showed that adding nebulized furosemide to salbutamol in RAD patients improved PEFR.